2014
DOI: 10.15512/joeoh/2014/v14i1-2/50734
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight Relationship and Growth Pattern of Common Carp <i>(cyprinus Carpio Var. Communis)</i> in Different Pond Environment in Mid Hill Region

Abstract: An experiment on rearing of common carp was carried out in three types of ponds viz. earthen pond, cemented tank and poly tank at field centre, DCFR, Champawat (Uttarakhand) and at selected farmers field of Champawat District to evaluate the growth performance of this fish species. ANCOVA results revealed that there are three distinct seasons which influence on length-weight relationship of common carp culture in these pond systems. The fish follows isometric growth in spring season (March-May); (however it do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The growth pattern in terms of length of the carp variety of the fish we used in this study is comparable with the species used in the study of Kumar et al. (2014). However, this study showed that P. tenebrifer and T. molitor fishmeal replacement results in longer C. carpio , which may have been due to the high protein content of P. tenebrifer and T. molitor (Gasco et al., 2016; Li et al., 2017).…”
Section: Discussionsupporting
confidence: 83%
“…The growth pattern in terms of length of the carp variety of the fish we used in this study is comparable with the species used in the study of Kumar et al. (2014). However, this study showed that P. tenebrifer and T. molitor fishmeal replacement results in longer C. carpio , which may have been due to the high protein content of P. tenebrifer and T. molitor (Gasco et al., 2016; Li et al., 2017).…”
Section: Discussionsupporting
confidence: 83%
“…Regression equations in aquaculture species are limited to Nile tilapia (He et al, ; Silva et al, ), rainbow trout (Gümüş & Balaban, ), common carp (Kumar et al, ) and Atlantic salmon (Beddow & Ross, ; Mørkøre et al, ). In contrast, for Neotropical farmed finfish, studies parameterizing regression equations for farmed traits are still scarce (Aguilar, Cruz, Mourao, & Cyrino, ; Furuya, Michelato, Cruz, & Furuya, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it serves two purposes: establish a mathematical relationship between dependent and independent variables and determine whether the growth type isometric or allometric (Shukla and Mishra 2017). Another biometric index used to assess fish status in their environment is the condition factor, a standard method to evaluate the overall species (Lim et al 2013;Kumar et al 2014;Seiyaboh et al 2016) and to know the growth ideal of fish (Latuconsina et al 2022). Based on the calculated length-weight relationship, the relative condition factor can be computed to determine when the observed and expected condition of the fish aligns (Srithongthum et al 2020) and the food reserves change (Datta et al 2013).…”
Section: Introductionmentioning
confidence: 99%